Use of bevacizumab as a single agent or in adjunct with traditional chemotherapy regimens in children with unresectable or progressive low‐grade glioma. (19th December 2018) - Zhukova, Nataliya; Rajagopal, Revathi; Lam, Adrienne; Coleman, Lee; Shipman, Peter; Walwyn, Thomas; Williams, Molly; Sullivan, Michael; Campbell, Martin; Bhatia, Kanika; Gottardo, Nicholas G.; Hansford, Jordan R.
Abstract: In pediatric low‐grade gliomas not amenable to complete resection, various chemotherapy regimens are the mainstream of treatment. An excellent overall survival of these patients makes justification of the intensification of chemotherapy difficult and calls for the development of new strategies. Bevacizumab, a humanized monoclonal antibody directed against Vascular endothelial growth factor (VEGF), has been successfully used in combination with irinotecan in a number of adult and pediatric studies and reports. Fifteen patients at median age of 7 years old (range 3 months to 15 years) were treated with bevacizumab in combination with conventional low‐toxicity chemotherapy. The majority had chiasmatic/hypothalamic and midline tumors, seven had confirmed BRAF pathway alterations including neurofibromatosis type 1 (2). Fourteen patients had more than one progression and three had radiotherapy. No deaths were documented, PFS at 11 and 15 months was 71.5% ± 13.9% and 44.7% ± 17.6% respectively. At the end of follow‐up 40% of patients has radiologically stable disease, three patients progressed shortly after completion of bevacizumab and two showed mixed response with progression of cystic component. Rapid visual improvement was seen in 6/8 patients, resolution of endocrine symptoms in 2/4 and motor function improvement in 4/6. No relation between histology or BRAF status and treatment response was observed. Treatment‐limiting toxicities included grade 4 proteinuria (2) and hypertension (2) managed with cessation (1) and pausing of therapy plus antihypertensives (1). In conclusion, bevacizumab is well tolerated and appears most effective for rapid tumor control to preserve vision and improve morbidity. Abstract : This study demonstrates that anti‐VEGF humanized monoclonal antibody bevacizumab is well tolerated and can be effectively used in pediatric patients with unresectable or progressive low‐grade glioma in combination with a number of conventional chemotherapies. Addition of bevacizumab to chemotherapy does not increase toxicity and allows for rapid control of clinical symptoms. However, optimal duration of therapy is yet to be determined in future studies.